Инглис ҳәм қарақалпақ тиллеринде референслерди салыстырмалы таллаў (FAN va JAMIYAT, 2018)
The article deals with the comparative analysis of references in English and Karakalpak languages. References are used in texts in the subject «Discourse analysis»: The authors of the article try to show the similar and different features of references in English and Karakalpak.